Physicochemical and microbiological quality of raw bovine milk in García Rovira, Santander: factors limiting its commercial viability - Castellanos Duarte, Frank Anderson; Esteban Bautista, Erika Yusmari; Castellanos Solano, Jisset Mayerling (Spei Domus, 2025)
The physicochemical and microbiological quality of raw bovine milk produced in the province of García Rovira, Santander, was evaluated over a 10-month period through the analysis of 440 samples collected from 1,376 farms distributed along 22 routes. Parameters measured included fat, protein, total solids, aerobic mesophilic counts, somatic cell count (SCC), and milk urea nitrogen (MUN). The results indicated that the milk met the minimum requirements for fat (3.69%), protein (3.31%), and total solids (12.31%). However, 82% of the samples exhibited aerobic mesophilic counts exceeding 1,000,000 CFU/mL, surpassing regulatory limits and hindering commercialization in markets that demand high quality standards. Additionally, 78.86% of the samples had SCC levels between 301 000 and 750 000 cells/mL, indicating a high prevalence of subclinical mastitis. The average MUN was 10 ± 2.11 mg/dL, although 30.23% of the samples showed values below 9 mg/dL, suggesting deficiencies in the animals’ protein intake. In conclusion, although the physicochemical quality of the milk is adequate, the high microbial loads and elevated somatic cell counts limit its commercial viability. This underscores the need to improve milking hygiene practices, enhance milk cooling infrastructure, and adjust cattle nutrition to ensure the sustainability and competitiveness of dairy production in García Rovira.